On the Issue of Distinguishing Individual and Group Training Activities in the Context of the Spread of the New Coronavirus Infection COVID-19 - D. A. Afanasev; K. S. Afanaseva (Теоретическая и прикладная юриспруденция)
The subject of the article is the issue of distinguishing individual and group training activities, the importance of which has increased in the context of the spread of the new coronavirus infection COVID-19. The authors consider the existing legal regulation in the field of organizing and conducting training events, as well as issues that arise in practice. Proposals are put forward to eliminate the existing “gaps” in the legislation.